Compensation and Child Privacy in the World of Influencers: Legal Challenges in Content Monetisation - Hamamah, Fatin (International Journal of Social Discussion, 2024)
In Indonesia, children are increasingly involved in income-generating social media content, especially on platforms such as YouTube and Instagram. While Child Protection Law No. 35/2014 protects children's basic rights, including from exploitation, there are no specific rules governing compensation for children who appear in digital content. This poses a problem in ensuring children get their just due. This legal loophole means that many children do not receive their rightful share of the revenue generated, and their privacy is often not protected. This article explores the challenges faced by children in the digital content industry in Indonesia, a topic that has not been widely addressed in national law. The purpose of this study is to analyse the legal status of children in monetised content in Indonesia and provide policy recommendations related to compensation and privacy rights. The method used is normative juridical with analysis of legislation and case studies from social media platforms. The results show that the legal protection of children in digital content is still inadequate, especially in supervision and public awareness. It is hoped that these results will encourage policy makers to immediately formulate rules related to compensation and children's privacy in the digital world.